Tobacco use in Haiti: findings from demographic and health survey - Bénédique Paul; David Jean Simon; Vénunyé Claude Kondo Tokpovi; Ann Kiragu; Ketty Balthazard-Accou; Evens Emmanuel (BMC Public Health, 2023)
Abstract Introduction Although tobacco has harmful effects on the physical and mental health of individuals, its use remains significant, according to the World Health Organization. To understand this phenomenon, studies have been carried out in many countries around the world, while in Haiti where more than 5,000 people die each year due to tobacco use, little is known about the use of this substance. The aim of this study was to examine the prevalence and the factors associated with tobacco use in Haiti. Methods We used data from the 2016/17 Haitian Demographic Health Survey. Both descriptive and multivariate analyses were conducted using STATA 16.0 software to assess the prevalence and identify factors associated with tobacco use. Results were reported as adjusted odds ratios with 95% confidence intervals. Statistical significance was declared at p < 0.05. Results The prevalence of tobacco use was estimated at 9.8% (95% CI: 9.2–10.4) among men and 1.7% (95% CI: 1.5–1.9) among women. Although the prevalence of tobacco use was low among young people, it increased with age. Respondents aged 35 and above, with no formal education, non-Christians, divorced/separated/widowed, from poorest households, rural areas, “Aire Métropolitaine de Port-au-Prince” region, with high media exposure had a higher likelihood of tobacco use. Conclusion The low prevalence of tobacco use among Haitian women and youth represents a public policy opportunity to prevent these vulnerable groups from starting smoking. Adult male smokers should also be targeted by appropriate policy to reduce the different health burdens associated with tobacco, both for the smokers and other people they may expose to passive smoking. Government and health sector stakeholders, along with community leaders, should create and enforce awareness strategies and rules to control advertisements that encourage irresponsible and health-risky consumption behaviors.